The Influence of Diary on the Students' Narrative Writing Skills Quasi-Experimental Study at UIN Syarif Hidayatullah, Jakarta - Dewi, Ratna Sari (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of the diary media on the ability to write narratives for Semester III students. The sample in this study was the 60th semester students of the Department of English Language Education at the Syarif Hidayatullah State Islamic University in Jakarta totalling 60 students. Sampling using a multistage random sampling technique. The method used is an experimental method, with non-equivalent experimental design. Data collection was performed using a narrative writing test and analysed using the t test. The results showed that the diary media had a significant effect on the ability to write student narratives with a coefficient of t count > table = 6.41> 1.70 at a significant level Î± = 0.05. These results indicate that the diary media can be used as an alternative media in learning to write student narratives. Therefore, teachers need to know the importance of using appropriate learning media to develop students' narrative writing skills.